2016
DOI: 10.1016/j.tetlet.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of extended oxazoles II: reaction manifold of 2-(halomethyl)-4,5-diaryloxazoles

Abstract: 2-(Halomethyl)-4,5-diphenyloxazoles are effective, reactive scaffolds which can be utilized for synthetic elaboration at the 2-position. Through substitution reactions, the chloromethyl analogue is used to prepare a number of 2-alkylamino-, 2-alkylthio- and 2-alkoxy-(methyl) oxazoles. The 2-bromomethyl analogue offers a more reactive alternative to the chloromethyl compounds and is useful in the C-alkylation of a stabilized (malonate) carbanion as exemplified by a concise synthesis of Oxaprozin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…2-Chloromethyl-4,5-diphenyloxazoles 1-3, versatile synthetic intermediates prepared in multi-gram quantities and in modest to good yields by methods previously reported from these laboratories, are the starting points. [23][24][25][26] The chloromethyl oxazoles 1-3 are reacted with 4-aminothiophenol in the presence of sodium hydride in THF to afford the 4-(aminothiophenyl)oxazoles 4-6 in yields ranging from 66% to 85%. Treatment of the (aminothiophenyl) oxazoles 4-6 with sodium nitrite in 10% aqueous HCl and sodium azide (5°C to rt, 16 h) gave the corresponding 4-azidophenylIJoxazolyl)sulfides 7-9 (61-98%) with no interference from the sulfide group.…”
Section: Design and Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…2-Chloromethyl-4,5-diphenyloxazoles 1-3, versatile synthetic intermediates prepared in multi-gram quantities and in modest to good yields by methods previously reported from these laboratories, are the starting points. [23][24][25][26] The chloromethyl oxazoles 1-3 are reacted with 4-aminothiophenol in the presence of sodium hydride in THF to afford the 4-(aminothiophenyl)oxazoles 4-6 in yields ranging from 66% to 85%. Treatment of the (aminothiophenyl) oxazoles 4-6 with sodium nitrite in 10% aqueous HCl and sodium azide (5°C to rt, 16 h) gave the corresponding 4-azidophenylIJoxazolyl)sulfides 7-9 (61-98%) with no interference from the sulfide group.…”
Section: Design and Chemistrymentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] In this report, we describe the syntheses and click reactions of similar 2,4,5-trisubstituted oxazole NITVK mimics. [23][24][25][26] These reacting components are now used in conjunction with sulfinylaryl-and sulfonylaryl-1,2,3-triazole linkers, albeit with the mono-and disubstituted aryl groups acting as the VXXLL structural mimic. Similar to the previous 'first-generation' compounds, the newly formed 1,2,3-triazole linker arising from the click reaction functions as the polar, slightly basic section of the entire peptidomimetic with the phenylsulfinyl or phenylsulfonyl portion allowing several more degrees of conformational freedom in the molecule's overall topology.…”
Section: Introductionmentioning
confidence: 99%
“…2) , a versatile intermediate reported previously from these laboratories which can be utilized to prepare extended oxazoles with diverse functionality. 6 Using a deprotonation/alkylation sequence, the α-methylenesulfone 1 offers an efficient hinge point for which to attach appendages that carry both the necessary azide and alkynyl functionalities prior to cyclization. Our previous studies showed that alkylation of 1 using potassium tert -butoxide/THF followed by addition of 1,6-dibromohexane provided the monoalkylated product 2a (53%) and not the expected cyclic product from double (intramolecular) alkylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using optimized conditions, oxidation of the naphthylmethyl isoindolinone derivative 12 did effect the expected conversion of the benzylic methylene to the carbonyl, but with accompanying bromination on the 2-position of the naphthyl ring to afford the monobromo derivative 21 (80%) (Scheme 3). Using isoindolinone ethyl ester 1 , LiHMDS and 2-bromomethyl-4,5-diphenyloxazole 23 as a co-reactant, 13 the expected β-oxazol-2-yl-(methyl)-substituted derivative 13 was isolated (63%, Table 1). Considering that the 2-substituted-4,5-diphenyloxazole group is a masked carboxyl equivalent, 14 the alkylation reaction gave essentially the aspartate derivative 13 with both carboxyl groups protected.…”
Section: Resultsmentioning
confidence: 99%